Electron Mobility in CdSexTe1-x (x = 0.25) Solid Solution: Ab Initio Calculation - O. P. Malyk (Фізика і хімія твердого тіла, 2020)
In this paper an assessment of the quality of a solid solution of CdSexTe1-x is done by study of itstransport properties. The description of the kinetic phenomena is carried on the base of the wave functionand self-consistent potential for solid solution CdSexTe1-x (x = 0.25) which were determined from the firstprinciples using the projector augmented waves as implemented in the ABINIT code. The scattering processeswere considered in the framework of short-range scattering models where the electron interaction with polar andnonpolar optical phonons, piezoelectric and acoustic phonons, static strain centers, neutral and ionized impuritieswas taken into account. The transition matrix elements were obtained by integration over the unit cell using threedimensionalB-spline interpolation. For crystals with impurity concentration 5.6*1015 - 5*1018 cm-3 thetemperature dependences of electron mobility and Hall factor in the range 15 - 1200 K are calculated. Thetheoretical curves obtained in the short-range approach differ qualitatively and quantitatively from thoseobtained within the long-range models in relaxation time approximation.